Electrically assisted pressure joining of titanium alloys. (October 2018) - Li, Yong-Fang; Das, Hrishikesh; Hong, Sung-Tae; Park, Ju-Won; Han, Heung Nam
Highlights: Ti alloy are solid-state joined by electrically assisted pressure joining (EAPJ). The strength and fracture mode of the joint are affected by the EAPJ parameters. An optimal thickness reduction exists for each value of current intensity. The optimal thickness reduction decreases as the current intensity increases. Abstract: Electrically assisted pressure joining (EAPJ) of a Grade 1 titanium (Ti) alloy is experimentally investigated. In EAPJ, an electric current is directly applied to the specimen during plastic compression. Microstructural analysis shows that solid-state joints are successfully fabricated in the selected Ti alloy without melting. Shear tensile tests shows that the strength and fracture modes of the joint are strongly affected by a combination of the amount of plastic deformation (corresponding to a thickness reduction) and the electric current intensity. An optimal thickness reduction, corresponding to the maximum fracture load, exists for each value of current intensity, and decreases as current intensity increases. A higher fracture load can be obtained by adjusting the combination of the current intensity and the thickness reduction parameters.